Comparison of soil and corn residue cutting performance of different discs used for vertical tillage - Zhiwei Zeng (Nature Portfolio, 2021)
Abstract High amount of corn (Zea mays L.) residue left in the field interferes with seeding operations, which hinders the viability of conservation agriculture. Vertical tillage is a promising practice in dealing with heavy crop residue, but its effectiveness largely depends on the design and use of tillage machines. In this study, three vertical tillage discs with different shapes, namely notched, plain, and rippled, were tested in a soil bin at two different working depths, shallow (63.5 mm) and deep (127 mm). Corn residues were spread on top of the soil as surface residue. soil cutting forces, soil displacement, and residue mixing with soil, as well as residue cutting were measured. The results showed that the working depth had a stronger effect on the performance of discs as compared to the disc type. No difference in residue cutting was found between the treatments. The deep working depth resulted in 5.1% higher residue mixing, 53.4% greater soil cutting forces, and 34.9% larger soil displacements, as compared to the shallow depth. The rippled disc resulted in the largest soil displacements with the greatest demand in soil cutting forces. Overall, the rippled disc was the most aggressive among the three discs with regard to the performance indicators measured. The results suggested that varying working depth would be an effective approach in changing the soil dynamics and residue cutting performance of the discs for vertical tillage.